2018
DOI: 10.3892/mmr.2018.9039
|View full text |Cite
|
Sign up to set email alerts
|

G protein‑coupled estrogen receptor/miR‑148a/human leukocyte antigen‑G signaling pathway mediates cell apoptosis of ovarian endometriosis

Abstract: The focus of the current study was a G protein‑coupled estrogen receptor (GPER)/microRNA (miR)‑148a/human leukocyte antigen‑G (HLA‑G) signaling pathway in ovarian endometriosis. Reverse transcription‑quantitative polymerase chain reaction was performed to analyze the changes in miR‑148a expression. A MTT assay, flow cytometry and caspase‑3/9 activity assays were performed to analyze cell proliferation, apoptosis and caspase‑3/9 activity levels, respectively. Protein expression was measured using western blot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…The expression of miR-152 is increased in the placental tissues and serum of PE, and this increased miR-152 expression can promote the apoptosis of trophoblast cells (32,33). Furthermore, miR-148a could modulate differentiation of MSCs (34), and the expression and function of miR-148a /152 were associated with estrogen signaling pathway (35)(36)(37)(38). All these findings suggest that miR-148a and miR-152 are key molecules mediating the function of E2 in MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR-152 is increased in the placental tissues and serum of PE, and this increased miR-152 expression can promote the apoptosis of trophoblast cells (32,33). Furthermore, miR-148a could modulate differentiation of MSCs (34), and the expression and function of miR-148a /152 were associated with estrogen signaling pathway (35)(36)(37)(38). All these findings suggest that miR-148a and miR-152 are key molecules mediating the function of E2 in MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations miRNA: microRNA; RISC: RNA-induced silencing complex; PDGF: Plateletderived growth factor; TGF: Transforming growth factor; PCD: Programmed [97] miR-503 Down-regulated Targeting BCL-2 mRNAs Treatment and biomarker [98] miR-183 Down-regulated Reducing apoptosis Treatment and biomarker [99] miR-29c Down-regulated Targeting c-JUN (a protein which regulates gene expression) Treatment and biomarker [100] miR-148a -Affecting BCL-2 expression and caspase-3/9 through G protein coupled estrogen receptor/miR148a/human leukocyte antigen G signaling pathway Treatment [101] miR-210 Up-regulated Inhibition of apoptosis by targeting signal transducer and activator of transcription 3…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HLA-G was expressed in both in situ and ectopic endometria of patients with adenomyosis, and HLA-G expression was also detected in ectopic endometrial lesions during menstruation. The findings suggest that epithelial cells carrying HLA-G may enter the peritoneal cavity during retrograde menstruation, allowing a local reaction of antigen with KIR2DL4 and mediating immune escape ( 168 170 ). A retrospective study showed that polymorphisms in HLA-G , LILRB1 , and LILRB2 genes contributed to the susceptibility and severity of endometriosis, but not KIR2DL4 polymorphisms ( 171 ).…”
Section: Unk Cells Under Pathological Conditionsmentioning
confidence: 99%